2022
DOI: 10.1152/ajpcell.00454.2021
|View full text |Cite|
|
Sign up to set email alerts
|

Control of coronary vascular resistance by eicosanoids via a novel GPCR

Abstract: Arachidonic acid metabolites epoxyeicosatrienoates (EETs) and hydroxyeicosatetraenoates (HETEs) are important regulators of myocardial blood flow and coronary vascular resistance (CVR), but their mechanisms of action are not fully understood. We applied a chemoproteomics strategy using a clickable photoaffinity probe to identify G protein coupled receptor 39 (GPR39) as a microvascular smooth muscle cell (mVSMC) receptor selective for two endogenous eicosanoids, 15-HETE and 14,15-EET, which act on the receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 62 publications
0
22
1
Order By: Relevance
“…However, the profile of oxylipins increased by HFD and GPR39 deletion is suggestive of increased neuroinflammation. We recently reported that GPR39 is an oxylipins receptor ( Alkayed et al, 2022 ); therefore, we report here valuable and unique oxylipins data that point to specific pathways altered in brain and plasma by HFD and GPR39 deletion, as potential mediators of cognitive impairment in these models. Another limitation is that we used a global GPR39 KO mouse model.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…However, the profile of oxylipins increased by HFD and GPR39 deletion is suggestive of increased neuroinflammation. We recently reported that GPR39 is an oxylipins receptor ( Alkayed et al, 2022 ); therefore, we report here valuable and unique oxylipins data that point to specific pathways altered in brain and plasma by HFD and GPR39 deletion, as potential mediators of cognitive impairment in these models. Another limitation is that we used a global GPR39 KO mouse model.…”
Section: Discussionmentioning
confidence: 87%
“…These diverse roles are believed to be related to the function of GPR39 as a receptor for zinc. More recently, we found that GPR39 also serves as a dual sensor for two eicosanoids with opposing actions on microvascular tone: the vasodilator 14,15-epoxyeicosatrienoate (14,15-EET) and vasoconstrictor 15-hydroxyeicosatetraenoate (15-HETE) ( Alkayed et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently reported that the G protein-coupled receptor 39 (GPR39) is a dual-ligand receptor regulated by AAderived oxylipins with opposing actions on inflammation and microvascular tone (Xu et al, 2021;Alkayed et al, 2022). GPR39 is a member of the ghrelin family of G proteincoupled receptors (GPCRs) that has recently been implicated in VCI (Davis et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%